Russia's food security and impact on agri-food trade - Linde Götz; Maximilian Heigermoser; Tinoush Jamali Jaghdani (Russia's role in the contemporary international agri-food trade system, 2022)
Russia's food policy has been defined by the quest for food security for more than a decade, which in the Russian context includes import protectionism, self-sufficiency, and import substitution, marked by the adoption of Food Security Doctrines in 2010 and 2020. This chapter first investigates the impact of food security policy on domestic production. Food security policy has combined with an increase in state support for domestic production, leading to notable increases in output and self-sufficiency for selected commodities. The chapter also examines the impact of food security on agri-food exports, which have become a priority since 2018. Although Russia has become a leading exporter of wheat, the influence of food security is seen by the introduction of export quotas on grain starting in 2020. Despite protectionism, Russia has not withdrawn from the international food market but rather is an active and significant player as both food importer and exporter.
Keywords: 630; Russia; food security policy; food security doctrine; self-sufficiency; import substitution; food exports